Epidemiology of Diabetic Ketoacidosis in the Waikato Region of New Zealand: 2000-2019 - Lynne Chepulis; Valentina Papa; Chunhuan Lao; Justina Wu; Cinthia Minatel Riguetto; Joanna M. McClintock; Ryan G. Paul (Journal of Diabetes Research)
Aims. Diabetic ketoacidosis (DKA) is not well characterised in New Zealand. This study is aimed at characterising the change in epidemiology and severity of DKA from 2000 to 2019 at a tertiary hospital in the Waikato region of New Zealand. Methods. A retrospective clinical data review of all patients admitted to Waikato District Health Board hospitals with DKA was undertaken. Characteristics and severity of DKA were assessed by type of DKA admission (diagnosed at admission, nonrecurrent, and recurrent), ethnicity, social deprivation, intensive care unit (ICU) admission, and length of hospital stay, with linear regression reporting on changes over time. Results. There were 1254 admissions for DKA (564 individual patients), two-thirds being recurrent events. Nonrecurrent DKA patients were younger, whilst recurrent admissions for DKA were associated with T1D, female gender, greater socioeconomic deprivation, and rural living (all P values < 0.01). DKA admission increased 8-fold between 2000 and 2019, mostly due to an increased number of recurrent events, particularly in Māori and female patients (P<0.001). ICU admissions increased over time (P<0.001) whilst length of hospital stay trended down (P=0.031). Conclusions. The rise in recurrent DKA is concerning, particularly in youth and indigenous Māori. Healthcare inequities need to be addressed, including adequate access to mental health support to ensure optimal outcomes for all patients with diabetes.